Lightweight certificateless linearly homomorphic network coding signature scheme for electronic health system - Yumei Li; Futai Zhang; Yinxia Sun (IET Information Security)
Abstract With the flourishing development of the Internet of Things (IoT), the electronic health system (EHS) as a leading technology has attracted widespread attention. However, the unsatisfactory network transmission throughput hinders practical applications of EHS to some extent. Network coding can solve this problem, but it also incurs another drawback called pollution attack. Pollution attack can be prevented by using homomorphic network coding signature schemes to check whether a corrupted packet is injected. However, existing schemes require high computational cost for signature verification which will reduce the transmission efficiency. A lightweight certificateless linearly homomorphic network coding signature scheme is proposed. This scheme requires a quite low computational cost when both signing and verifying a data packet. In addition, it is proved that the scheme is secure, and it was implemented by using the Java Pairing‐Based Cryptography Library (JPBC) on a personal computer (PC). The simulation results illustrate that our scheme is efficient.